Fungicides performance to control wheat leaf diseases - Kuhnem Junior, Paulo Roberto; Casa, Ricardo Trezzi; Rizzi, Fábio Pontel; Moreira, Eder Novaes; Bogo, Amauri (Revista de Ciências Agroveterinárias, 2009)
The objective of this work was to evaluate the effect of fungicides azoxystrobin (75g i.a./ha), azoxystrobin + ciproconazol (60g+24g), azoxystrobin (50g) + propiconazol (62,5g), propiconazol (125g), propiconazol + ciproconazol (75g+24g), pyraclostrobin + epoxiconazol (100g+37,5g), tebuconazol (150g) e trifloxystrobin + tebuconazol (75g+150g) to control wheat leaf diseases in cultivars Ônix and BRS Louro. The fungicides application was made by handle spray, with pressure generated by a flow rate of 200 L ha-1 of CO2, during the growth stages of four open leaves and elongation. Leaf incidence and severity were quantified at 7, 14, 21 and 28 days after each application. The chemical control with fungicide provided significant increase on grain yield and weight of a thousand grains in both cultivars. There was no significant difference between fungicides in both cultivars, showing control efficiency over 70% by the severity criterion in the second application. The mixture of triazol and strobilurins had better control of leaf diseases in both cultivars.